The The Role of Consumer Satisfaction Mediation in the Relationship Between Consumer Trust, Service Quality, and Rental Costs on the Interest in Renting Heavy Equipment at CV. Berkat Bersama - Sonia Nengsih sonia Negsih; Pardiman; Ridwan Basalamah (LP2M IAIN Palopo, 2026)
This study examines the mediating role of consumer satisfaction in the relationship between consumer trust, service quality, rental costs, and rental interest in heavy equipment at CV. Berkat Bersama. The purpose is to understand how these factors influence rental decisions and how satisfaction strengthens consumer trust toward rental intention. Using a quantitative approach, data were collected through questionnaires from 100 respondents and analyzed using SmartPLS. The findings show that consumer trust significantly affects rental interest, service quality, and satisfaction. Furthermore, consumer satisfaction mediates the relationship between consumer trust and rental interest, indicating that higher trust enhances satisfaction, which in turn increases rental intention. However, satisfaction does not mediate the effect of service quality and rental costs on rental interest, implying that these variables influence intention through other channels. The study highlights that trust is the most dominant factor shaping rental interest, while service quality and competitive pricing remain essential to sustain customer satisfaction. Theoretically, the research reinforces consumer behavior and relationship marketing models, emphasizing the importance of trust and satisfaction. Practically, it suggests that companies should focus on trust-building, improving service consistency, and ensuring transparent pricing to strengthen competitiveness and increase heavy equipment rental interest.